2019
DOI: 10.1016/j.jbusres.2019.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and financial stability in US banks: Do indirect interlocks matter?

Abstract: In the context of the Depository Institution Management Interlocks Act of 1978 (Interlocks Act), we investigate the structure and implications of the professional connections among bank directors. Based on a hand-collected unique dataset for a sample of 168 US commercial banks listed continuously from 2009 to 2015, we find that the barriers set out in the Interlocks Act have been circumvented by the establishment of indirect interlocks that allow for mass professional connections among bank directors. Our evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 138 publications
(227 reference statements)
1
22
1
Order By: Relevance
“…Indeed, the small number of women directors on the AC as well as the need to improve their effectiveness are the major reasons for their low monitoring role (Salleh & Haat, 2013). This result is inconsistent with agency and resource dependence theories, as well as, the findings of several studies in developed countries such as Gavious et al (2012), Gul et al (2007), Thiruvadi andHuang (2011), andZalata et al (2018), and a few studies in Malaysia such as Ku Ismail and Abdullah (2013) and Salleh et al (2012), which found a negative relationship between women directors on the AC and EM; that is, women on the AC significantly enhance the quality of financial reporting.…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…Indeed, the small number of women directors on the AC as well as the need to improve their effectiveness are the major reasons for their low monitoring role (Salleh & Haat, 2013). This result is inconsistent with agency and resource dependence theories, as well as, the findings of several studies in developed countries such as Gavious et al (2012), Gul et al (2007), Thiruvadi andHuang (2011), andZalata et al (2018), and a few studies in Malaysia such as Ku Ismail and Abdullah (2013) and Salleh et al (2012), which found a negative relationship between women directors on the AC and EM; that is, women on the AC significantly enhance the quality of financial reporting.…”
Section: Resultscontrasting
confidence: 57%
“…Hence, they may strengthen the monitoring role of the AC in improving the quality of earnings and financial reporting, aligning with the theories of agency and resource dependence. Most previous studies such as Gavious et al (2012), Gul et al (2007), Thiruvadi andHuang (2011) Zalata, Tauringana, andTingbani (2018) have concluded that, in developed countries, women on the AC positively influence the quality of financial reporting, measured by EM. Similarly, studies by Ku Ismail and Abdullah (2013), Salleh, Hashim, andMohamad (2012), andZalata, Tauringana, andTingbani (2018) have concluded that, in Malaysia, women on the AC positively influence the quality of financial reporting, measured by EM.…”
Section: Women On the Audit Committee (Ac)mentioning
confidence: 94%
See 2 more Smart Citations
“…It is also reported that low liquidity has a significant and negative effect on bank compliance to rule and regulations that have proposed by Basel III. So, the bank would comply less to hold high ratio of capital as required, once attract more deposits and grant more loans, which means more illiquid assets (Abdelbadie & Salama, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%